Frequency of Neonatal Thrombocytopenia in Pregnant Women Complicated by Idiopathic Thrombocytopenia (Medical Forum Monthly, 2020)
Objective: To find out the frequency of neonatal thrombocytopenia in pregnant women complicated by idiopathic thrombocytopenia.Study Design: Cross sectional surveyPlace and Duration of Study: This study was conducted at the Department of Obstetrics & Gynecology Sandeman Provincial Hospital Bolan Medical Complex Hospital Quetta from 15th January i2019 to 30th October 2019.Materials and Methods: After approval from the ethical committee of the institution 60 pregnant patients of age range between more than 18 and less than 35 diagnosed idiopathic thrombocytopenia on laboratory investigation with platelets <100-10.Results: The mean age of the patients included in the study was 32.53 i+ 3.82 years [range 18 i–35]. There were i34(56.67%) patients of age range of 31-35 years, 20 (33.33%) patients of age range of 26 – 30 years, i6 (10%) patients of age range of 18 – 25 years, 27(45%) were between 32-36 weeks of gestation, 24 (40 i%) were between i37-40 weeks; and 9(15%) were recorded with >40 weeks of gestation, frequency of neonatal thrombocytopenia was recorded in 33(55%) of cases, 14(42.43%) cases were with severe thrombocytopenia,i11(33%) had moderate and 8(24.24%) mild anemia.Conclusion: The frequency of neonatal thrombocytopenia is high among patients with in pregnant women complicated by idiopathic thrombocytopenia.